A formação da identidade: o paradoxo como gerador do único - Lean, Tamine José (1985)
The present study, intends to amplity the comprehension of the identity's formation. It wants to give the dimensions of the mechanisms involved in paradox, which works in the individual's development, permiting that himself be unique. In this sense, it evaluates the conception of the man and it delimitates the identity's definition, in which this study is based. Later on, defines the paradox and situates its role in the identity's formation. The justification of this study, between others, is inserted in the necessity of the comprehension the identity's structure, and the agents that operate itself, offering subsidy for a adjust actuation of the professionals that labor, more directly, with the individual's conformations as much danger as precious and difficult task. The identity inserts the change in the continuity, to ignore its basics interactions is to drive it for aleatory routes, and, anyway, to avoid to considerate the philosophical, anthropological and ethical questions, contained in interactions. Between the fundamentals conclusions: those a) the structuration of the individual occurs when he faces the paradox; b) the identity's concept transcends the definitions that designate the equality (in the time), singularity, selfconcept, and so on, it must integrate themselves within the concept of 'social identity'; c) the paradox may be constructed or desintegrated by the experience; d) the identity's integrity is expressed when the integration between the paradox’s elements occurs.